Protonation‐Driven Polarization Retention Failure in Nano‐Columnar Lead‐Free Ferroelectric Thin Films - Muhammad Sheeraz; Chang Won Ahn; Nguyen Xuan Duong; Soo‐Yoon Hwang; Ji‐Soo Jang; Eun‐Young Kim; Yoon Ki Kim; Jaeyeong Lee; Jong Sung Jin; Jong‐Seong Bae; Myang Hwan Lee; Hyoung‐Su Han; et al. (Advanced Science)
Abstract Understanding microscopic mechanisms of polarization retention characteristics in ferroelectric thin films is of great significance for exploring unusual physical phenomena inaccessible in the bulk counterparts and for realizing thin‐film‐based functional electronic devices. Perovskite (K,Na)NbO3 is an excellent class of lead‐free ferroelectric oxides attracting tremendous interest thanks to its potential applications to nonvolatile memory and eco‐friendly energy harvester/storage. Nonetheless, in‐depth investigation of ferroelectric properties of (K,Na)NbO3 films and the following developments of nano‐devices are limited due to challenging thin‐film fabrication associated with nonstoichiometry by volatile K and Na atoms. Herein, ferroelectric (K,Na)NbO3 films of which the atomic‐level geometrical structures strongly depend on thickness‐dependent strain relaxation are epitaxially grown. Nanopillar crystal structures are identified in fully relaxed (K,Na)NbO3 films to the bulk states representing a continuous reduction of switchable polarization under air environments, that is, polarization retention failures. Protonation by water dissociation is responsible for the humidity‐induced retention loss in nano‐columnar (K,Na)NbO3 films. The protonation‐driven polarization retention failure originates from domain wall pinning by the accumulation of mobile hydrogen ions at charged domain walls for effective screening of polarization‐bound charges. Conceptually, the results will be utilized for rational design to advanced energy materials such as photo‐catalysts enabling ferroelectric tuning of water splitting.